2012
DOI: 10.1089/jpm.2011.0442
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Uncertain Terrain: A Qualitative Analysis of Clinicians' Experiences of Refractory Suffering

Abstract: In palliative care, the witnessing of unrelieved (refractory) suffering takes its toll on all concerned; however, the effect on experienced palliative clinicians of witnessing such suffering has largely been unexplored. The aim of this study was to examine health care professionals' (nurses, doctors, and allied health workers) experiences of working with a patient's refractory suffering, together with their clinical management strategies. A qualitative research design involving semistructured interviews and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…7,[16][17][18]20,21 In this study, the participants identified their main goals as optimizing their patients' QOL and orchestrating a peaceful death for the patient. Bounded by the context of the nursepatient relationship, the participants observed, assessed issues, identified suffering, and intervened to relieve their patients' suffering.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…7,[16][17][18]20,21 In this study, the participants identified their main goals as optimizing their patients' QOL and orchestrating a peaceful death for the patient. Bounded by the context of the nursepatient relationship, the participants observed, assessed issues, identified suffering, and intervened to relieve their patients' suffering.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,16,17,20 In essence, each aspect of suffering is seen as a separate issue instead of one component of the larger issue of ''suffering.'' For example, pain is considered a physical issue until declining functional status and resultant role changes are factored in as part of the larger relational context of what the pain means and is doing to the patient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations